Improving Technologies of Integrative Approach to Mother Language and Reading Literacy Lessons (Eurasian Journal of Learning and Academic Teaching, 2023)
New Uzbekistan requires a new approach to education. Therefore, it is appropriate to look at the approach with the requirement of integration into school education as a result. To develop the spirituality of the young generation, to familiarize them closely with the rich history, national values, traditions and literary and artistic heritage of the Uzbek people, to develop the national and universal values formed on the basis of national traditions